Maternal Health Related Characteristics and Economic Condition as Impacting Factors for the Low Birth Weight of Children in Bangladesh - Kabir, Md Ahsanul; Tania, Motahara Islam; Hossain, Zenat Zebin (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Low birth weight (LBW) is a leading concern for public health in many developing countries, including Bangladesh. Objective: To identify the association of mothers’ health related characteristics and family economic condition with low birth weight of children in Bangladesh with a countrywide data. Methods: A total of 2204 child data were used from Bangladesh demographic and health survey (BDHS) 2017. Descriptive analyses were performed for social and demographic characteristics. Logistic regression model was used to present mothers’ health related characteristics and family economic condition with low birth weight and results were described in terms of odds ratio (OR) with 95% CI for both adjusted (aOR) and unadjusted (uOR) models. Results: Odds of having low birthweight is 37% higher (aOR=1.37, 95% CI= 0.75, 2.46) among the unplanned children. Odds of having low birthweight for children is also higher among the children when mother received iron and vitamin supplementation during their childbirth. However, those associations were not statistically significant in both adjusted and unadjusted model. In addition, odds of having low birthweight are higher among the children of that mother who has low BMI. However, this association was also not statistically significant. Prevalence of low birthweight was 21.7% among the children from middle class families, while it was 12.71% in rich families. The difference was statistically significant. Odds of having low birthweight in children is less among the poorer is 41% less (aOR= 0.59, 95% CI= 0.37, 0.95) and among the richest is 48% less (aOR= 0.52, 95% CI= 0.31, 0.89) as compared to the children from poorest economic status. All of those associations in adjusted and unadjusted model were significant (P<0.05) for poorer and richest family. Prevalence of low birthweight is 21.26% vs 14.11% among the unwanted and wanted children in the rural area and this difference is statistically significant. Conclusion: The prevalence of low birthweight among children is high in the poor community in comparison to rich families in Bangladesh. Unplanned children are at risk of having low birth weight in comparison to planned pregnancy. Special antenatal care should be given to mothers who have low-economic status. International Journal of Human and Health Sciences Vol. 07 No. 04 Oct’23 Page: 301-308